ANALISIS PERHITUNGAN HARGA JUAL PRODUK DENGAN DASAR HARGA POKOK PESANAN METODE FULL COSTING STUDI PADA UD. KUBE MAWAR PUTIH - Gendis Hardiyanti Aprilia; Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This study aims to determine the product selling price based on the order price of UMKM UD. Kube Mawar Putih. Data is obtained by means of interviews and documentation studies and analyzed by comparing the calculation of the production cost which has been carried out by the company with the calculation of the cost of goods with the full costing method. The result of the study show that the difference in advantegous if the company uses the calculation of full costing method.